2019
DOI: 10.1371/journal.pmed.1002762
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal malaria chemoprevention combined with community case management of malaria in children under 10 years of age, over 5 months, in south-east Senegal: A cluster-randomised trial

Abstract: BackgroundSeasonal malaria chemoprevention (SMC) is recommended in the Sahel region of Africa for children under 5 years of age, for up to 4 months of the year. It may be appropriate to include older children, and to provide protection for more than 4 months. We evaluated the effectiveness of SMC using sulfadoxine-pyrimethamine plus amodiaquine given over 5 months to children under 10 years of age in Saraya district in south-east Senegal in 2011.Methods and findingsTwenty-four villages, including 2,301 childre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
53
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(67 citation statements)
references
References 20 publications
2
53
0
Order By: Relevance
“…An improvement of haemoglobin level (Table 1) was observed over the intervention period (September to November). The above observations could be attributed to SMC as it has been shown in many other studies about the protective effect of SMC on malaria in children in Africa [12][13][14]. The regular monthly administration of SP + AQ allows maintenance of drug concentration in blood and prevents parasite growth and avoids red blood cell destruction, which in turn prevents haemoglobin level decrease by malaria parasites [14,15].…”
Section: Discussionmentioning
confidence: 58%
See 1 more Smart Citation
“…An improvement of haemoglobin level (Table 1) was observed over the intervention period (September to November). The above observations could be attributed to SMC as it has been shown in many other studies about the protective effect of SMC on malaria in children in Africa [12][13][14]. The regular monthly administration of SP + AQ allows maintenance of drug concentration in blood and prevents parasite growth and avoids red blood cell destruction, which in turn prevents haemoglobin level decrease by malaria parasites [14,15].…”
Section: Discussionmentioning
confidence: 58%
“…IPT during the malaria transmission season improved malaria epidemiological trends in children [16]. A substantial reduction of malaria indicators in children was already reported in Mali [8,12] and elsewhere in Africa [14,17,18], which was attributed to SMC implementation in addition to other control interventions, such as IPT and LLINs. The beneficial effect of SMC on malaria clinical incidence has been reported by many other studies [15,19,20].…”
Section: Discussionmentioning
confidence: 87%
“…young children and pregnant women, but also older children and adults of all age in Kobeni. In this context, seasonal ASAQ Artesunate-amodiaquine, AL Artesunate-lumefantrine, SP Sulfadoxinepyrimethamine, CQ Chloroquine, AS-SP Artesunate-sulfamethoxypyrazine-pyrimethamine malaria chemoprevention (SMC) could be useful in preventing malaria episodes and associated parasitaemia and anaemia in children under 5 years and even in older children (up to 10 years) in the region [40]. Indeed, SMC was recommended in 2012 by the WHO for children aged 3-59 months living in areas with highly seasonal malaria transmission, as in the Sahelian region in Africa [41].…”
Section: Discussionmentioning
confidence: 99%
“…In Senegal, the neighboring country, JL Ndiaye et al found a substantial bene t of SMC among children 5-9 years of age, on hemoglobin and the prevalence of parasitemia (8). Several studies have shown the epidemiological impact of SMC in school age children in clinical trials (8)(9)(10). Touré et al in 2016 found that the proportion of children over 5 years of age carrying malaria parasites was higher in all seasons compared to younger children in Sélingué, Mali due to malaria control policy focused on children under ve and pregnant women.…”
Section: Introductionmentioning
confidence: 98%
“…(7). In Senegal, the neighboring country, JL Ndiaye et al found a substantial bene t of SMC among children 5-9 years of age, on hemoglobin and the prevalence of parasitemia (8). Several studies have shown the epidemiological impact of SMC in school age children in clinical trials (8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%